Epoxy networks containing large mass fractions of a monofunctional Polyhedral Oligomeric Silsesquioxane (POSS) - Abad, María J. (2003)
A polyhedral oligomeric silsesquioxane (POSS) containing one epoxy group and seven isobutyl groups per molecule was incorporated into an epoxy network following a two-stage process. In the first stage, POSS was reacted with an aromatic diamine, employing a 1:1 molar ratio of both reactants. The distribution of species at the end of reaction, determined by size exclusion chromatography (SEC), was close to the ideal one. In a second step, this precursor was reacted with the stoichiometric amount of an aromatic diepoxide to generate an organic-inorganic hybrid material containing 51.8 wt% POSS. A primary liquid-liquid phase separation process occurred at the time of adding the diepoxide to the POSS-diamine precursor. This led to a macrophase separation into epoxy-rich and POSS-rich regions, possibly derived from the incompatibility of the isobutyl groups attached to the POSS with the aromatic epoxy-amine network. A secondary phase separation occurred in the epoxy-rich phase in the course of polymerization, producing a dispersion of small POSS domains. Both modulated local thermal analysis (LTA) and differential scanning calorimetry (DSC) showed that most POSS-rich domains were amorphous. A small fraction of POSS crystals was also detected. A postcure cycle led to an increase in the glass transition temperature and the disappearance of crystallinity. A reference network was synthesized by replacing POSS by phenyl glycidyl ether (PGE) in equimolar amounts. The resulting network was homogeneous but exhibited a lower glass transition temperature than the POSS-modified network. As both networks had the same topology, the higher Tg observed for the POSS-modified epoxy may be associated with the hindering of polymer chain motions by their covalent bonding to POSS clusters. The most important concept arising from these results is that a phase separation process may take place when employing a POSS bearing organic groups that are not compatible with the epoxy network.